2012
DOI: 10.1098/rsbl.2012.0435
|View full text |Cite
|
Sign up to set email alerts
|

It pays to cheat: tactical deception in a cephalopod social signalling system

Abstract: Signals in intraspecific communication should be inherently honest; otherwise the system is prone to collapse. Theory predicts, however, that honest signalling systems are susceptible to invasion by cheats, the extent of which is largely mediated by fear of reprisal. Cuttlefish facultatively change their shape and colour, an ability that evolved to avoid predators and capture prey. Here, we show that this ability is tactically employed by male mourning cuttlefish ( Sepia plangon ) to mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
70
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(79 citation statements)
references
References 18 publications
6
70
0
Order By: Relevance
“…As seen in the well-studied examples of male mimicry in some insects and lizards (Svensson et al, 2009), this could provide a selective advantage during periods of male aggression, but a disadvantage when mates are scarce; in insects and lizards, this mimicry varies as a result of genetic polymorphism, while in the squid, it could vary dynamically under neuronal control. Cuttlefish, Sepia apama (Hanlon et al, 2005) and Sepia plangon (Brown et al, 2012), have been shown to use rapid reversible sexual mimicry in mating interactions, but in these cases it is the males that mimic female coloration to stealthily gain access to female mates.…”
Section: Discussionmentioning
confidence: 99%
“…As seen in the well-studied examples of male mimicry in some insects and lizards (Svensson et al, 2009), this could provide a selective advantage during periods of male aggression, but a disadvantage when mates are scarce; in insects and lizards, this mimicry varies as a result of genetic polymorphism, while in the squid, it could vary dynamically under neuronal control. Cuttlefish, Sepia apama (Hanlon et al, 2005) and Sepia plangon (Brown et al, 2012), have been shown to use rapid reversible sexual mimicry in mating interactions, but in these cases it is the males that mimic female coloration to stealthily gain access to female mates.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, visual signals are sometimes accompanied by a behavioural display (Bitton and Doucet ), so the signal becomes more conspicuous. Such displays are common in many taxa such as molluscs (Brown et al ), arthropods (crustaceans, Arnott and Elwood ; insects, Brown and Porras ) and chordates (reptiles, Eifler and Eifler ; birds, Andersson and Iwasa , Bitton and Doucet ; or mammals, Gol'din ). They may have evolved to amplify information conveyed in visual signals emitted to conspecifics (in intra‐ or intersexual contexts) as well as to heterospecifics.…”
Section: Framework Of Predictions For the Different Hypotheses (Not Mmentioning
confidence: 99%
“…This flexible use of behaviour includes the active falsification of signals and the withholding of specific signals 5,6 . Current evidence for tactical deception comes primarily from either anecdotal reports or captive studies across several taxa [7][8][9][10] , with rather limited empirical evidence coming from wild/freeranging populations [11][12][13] .…”
mentioning
confidence: 99%